9th Judgement - Patterson, James with Paetro, Maxine (London Century, 2010)
A young woman and her infant child are ruthlessly gunned down while returning to their car in the garage of a shopping mall. Detective Lindsay Boxer discovers only one shred of evidence: a foreboding and cryptic message written in blood red lipstick on a windshield. The same night, the wife of A-list actor Marcus Dowling walks in on a cat burglar. In just seconds there is an empty safe, a lifeless body, and another mystery that throws San Francisco into hysteria. With two criminals to capture, and her lust for Rich challenging her love for Joe, Lindsay summons her friends in the Women s Murder Club. Lindsay is asked to put her own life on the line but will it be enough? "
Keywords: Murder--Investigation